Impact of Belatacept Conversion on Renal Function, Histology, and Gene Expression in Kidney Transplant Patients With Chronic Active Antibody-mediated Rejection. Issue 3 (22nd February 2021) - Kumar, Dhiren; Raynaud, Marc; Chang, Jessica; Reeve, Jeff; Yakubu, Idris; Kamal, Layla; Levy, Marlon; Bhati, Chandra; Kimball, Pamela; King, Anne; Massey, Davis; Halloran, Philip; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Here, we present our initial experience with a prospective protocol of belatacept conversion in patients with chronic active antibody-mediated rejection (caAMR) and a high degree of chronicity at the time of diagnosis. Methods: We converted 19 patients (mean age, 45 ± 12 y) with biopsy-proven caAMR from tacrolimus to belatacept at a median of 44 months post–kidney transplant. Results: At a median of 29 months (interquartile range, 16–46 mo) postconversion, death-censored graft and patient survivals were 89% and 95%, respectively. When compared to a 1:2 propensity-matched control cohort from the INSERM U970 registry maintained on calcineurin inhibitor, the belatacept group had progressive improvement ( P = 0.02) in estimated glomerular filtration rate from a mean of 33.9 ± 10 at baseline to 37.8 ± 13 at 6 months and 38.5 ± 12 mL/min/1.73 m 2 at 12 months postconversion, as compared to a steady decline noted in the controls (36.2 [baseline] → 33.1 [6 mo] → 32.7 mL/min/1.73 m 2 [12 mo] of follow-up). A paired histologic comparison of preconversion and postconversion (performed at median 9.5 mo postconversion) biopsies showed no worsening in microvascular inflammation or chronicity. The paired tissue gene expression analysis showed improved mean total rejection score (0.68 ± 0.26–0.56 ± 0.33; P = 0.02) and a trend toward improved antibody-mediated rejection score (0.64 ± 0.34–0.56 ± 0.39; P = 0.06). Conclusions: Here, we report that in patients diagnosed with caAMR who were not subjected to intensive salvage immunosuppressive therapies, isolated belatacept conversion alone was associated with stabilization in renal function. These results are bolstered by molecular evidence of improved inflammation.